THE EFFECT OF SEVERITY, ASSET RETRENCHMENT, DOWNSIZING AND LEVERAGE ON THE SUCCESS OF CORPORATE TURNAROUND WITH PROFITABILITY AS A MODERATING VARIABLE - Darmayanti, Novi; Fazira P, Erra; Jamil, Amira; Waedaramae, Waefatimoh (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research was conducted with the aim of finding out the influence of severity, asset retrenchment, downsizing, and leverage on the success of corporate turnaround with profitability as a moderating variable in tourism sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Method: Testing in this research uses the SmartPLS program using the moderated regression analysis method. Results:  Based on the results of the bootstrapping test, it shows that severity and leverage have an effect on the success of the company's turnaround, while downsizing and asset retrenchment have no effect on the success of the company's turnaround. Based on the results of the bootstrapping test, profitability can moderate the influence of leverage on the success of a company's turnaround, while profitability cannot moderate the influence of severity, asset retrenchment, and downsizing. Novelty: The study provides insights into the role of profitability as a moderating variable in the relationship between leverage and corporate turnaround success, highlighting that it does not moderate the influence of severity, asset retrenchment, and downsizing.